Advanced Oxidation Processes for Carmoisine (E122) Dye in UV-A/ZnO System: Influencing PH, Temperature and Oxidant Agents on Dye Solution - Luma Majeed Ahmed (Journal of Global Pharma Technology, 2018)
This paper aims to estimate the effects ofthree operating parameters such asinitial pH, temperature and oxidant agents (like H2O2 and Fe2+) on the stability of the food azocarmoisine dye under UV-A/ carmoisine/ ZnO system. The performed experiments in this work proved that the optimum initial pH is at zero point charge of ZnO and equal to 9.14 and with efficiency % equal to 90.936 at 8 min. The study of temperature was enhanced this photo reaction with activation energy equal to7.562 kJ mol-1.The addition of oxidant agents to an aqueous solution of carmoisine dye was declined the activity of decolorization, that referred to the addition of these compound will increase the resistance of carmoisine dye to light. The quantum yield ( ) for decolorization of carmoisine dye with the using ZnO without and with the using oxidant agent (H2O2 and Fe2+) was following to the sequences:  without the oxidant agent >  with the using oxidant agent (H2O2) > with the using oxidant agent (Fe2+) and equal to 0.485, 0.279 and 0.141 respectively.The physical deactivated process mostly was dominated on this photoreaction.From the other word, the addition of oxidant agents is useful to decrease the degradation of this dye when used it in food's industries.Keywords: Carmoisine dye, Food red 3, acid red 14 dye, Azorubine, Oxidant reagents, food's dye.